Sosialisasi Pemanfaatan Metode Tabulampot sebagai Alternatif Dalam Meningkatkan Produktivitas Lahan Pekarangan di Desa Gelangsar, Kabupaten Lombok Barat - Baiq Farista; Arben Virgota; Suripto; Ahmad Jupri; Nur Indah Julisaniah; Dining Aidil Candri (Universitas Mataram, 2022)
Gelangsar Village, West Lombok Regency has a hilly topography and steep slopes. This condition causes low soil fertility in several locations, especially locations with steep slopes. The hills around the village of Gelangsar also affect the incoming light intensity. Resident around the hillsides, complained that the fruit trees in their yards could not bear fruit even though they were more than 10 years old. The solution offered to overcome these problems is the application of the tabulampot method. This program aims to introduce and apply the tabulampot method in the yard. The Tabulampot method is expected to provide maximum fruit crop yields. The method used in this program is socialization and tabulampot pilot project. The socialization method used was counseling and distribution of leaflets (brochures), while the application of tabulampot was carried out through the establishment of a pilot project. This program has been successfully. The participants actively asked questions in discussion sessions and also in the practice of making tabulampot. Tabulampot has a great opportunity to be implemented in the Gelangsar Village because it is easy and cheap.